2018
DOI: 10.5152/eurjrheum.2018.17194
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic antibodies in patients with systemic lupus erythematosus

Abstract: Objective: Antibodies with catalytic (hydrolytic) properties to DNA or RNA have been reported in systemic lupus erythematosus (SLE). However, it is well known that ethnicity plays an important role in the presentation of SLE and severity of the disease; hence, these data may not truly represent a general feature of all SLE patients. Therefore, we have analyzed the hydrolyzing activity of immunoglobulin G (IgG) of SLE patients from the Indian population with an aim to decode whether the catalytic antibody respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Septicemia is the most common cause of death in intensive care units, and it is caused by the toxic host’s systemic response to infection [ 36 , 168 ]. With the widespread use of antibiotics, the incidence of septicemia caused by opportunistic pathogens has gradually increased in recent years, with the increase in drug-resistant strains, showing a trend of multidrug resistance [ 169 , 170 ].…”
Section: Application Of Catalytic Antibodies In the Field Of Infectio...mentioning
confidence: 99%
See 4 more Smart Citations
“…Septicemia is the most common cause of death in intensive care units, and it is caused by the toxic host’s systemic response to infection [ 36 , 168 ]. With the widespread use of antibiotics, the incidence of septicemia caused by opportunistic pathogens has gradually increased in recent years, with the increase in drug-resistant strains, showing a trend of multidrug resistance [ 169 , 170 ].…”
Section: Application Of Catalytic Antibodies In the Field Of Infectio...mentioning
confidence: 99%
“…Catalytic antibodies have been proposed to be involved in the removal of metabolic waste and the prevention of infection. It has been shown that high levels of catalytic antibodies are associated with a good prognosis of septicemia [ 36 , 168 ]. IgG with serine protease-like hydrolysis activity is present in the plasma of the patients.…”
Section: Application Of Catalytic Antibodies In the Field Of Infectio...mentioning
confidence: 99%
See 3 more Smart Citations